2012
DOI: 10.1111/j.1600-6143.2012.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmyeloablative Conditioning Generates Autoantigen-Encoding Bone Marrow That Prevents and Cures an Experimental Autoimmune Disease

Abstract: Autoimmune diseases result from chronic targeted immune responses that lead to tissue pathology and disease. The potential of autologous hematopoietic stem cells transplantation as a treatment for autoimmunity is currently being trialled but disease relapse is an issue. We have previously shown in a mouse model of experimental autoimmune encephalomyelitis (EAE) that the transplantation of bone marrow (BM) transduced to encode the autoantigen myelin oligodendrocyte glycoprotein (MOG) can prevent disease inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…13 In our study published in The American Journal of Transplantation, the principle aim was to assess if the protocol of transplanting transduced BM encoding MOG could be employed in the EAE model with non-myeloablative preconditioning to promote long-term remission. 19 The study confirmed that we could utilize non-myeloablative conditioning but also reconfirmed earlier observations that only low levels of chimerism are required to achieve this. Even with chimerism levels of a few percent, tolerance was complete and animals with established EAE remained resistant to relapse in the presence of rechallenge with self-antigen.…”
supporting
confidence: 74%
“…13 In our study published in The American Journal of Transplantation, the principle aim was to assess if the protocol of transplanting transduced BM encoding MOG could be employed in the EAE model with non-myeloablative preconditioning to promote long-term remission. 19 The study confirmed that we could utilize non-myeloablative conditioning but also reconfirmed earlier observations that only low levels of chimerism are required to achieve this. Even with chimerism levels of a few percent, tolerance was complete and animals with established EAE remained resistant to relapse in the presence of rechallenge with self-antigen.…”
supporting
confidence: 74%
“…Another important aspect of BM transplantations in this setting is the degree of toxicity and mortality associated with the preconditioning regimes (4). Positive inroads are being made on this front, and we have recently shown in our studies that a nonmyeloablative preconditioning regimen can be used to reproduce tolerance to MOG in our EAE model (45). Underpinning this is the observation that only low-level microchimerism is required to promote robust tolerance (45,59).…”
Section: Discussionmentioning
confidence: 99%
“…Positive inroads are being made on this front, and we have recently shown in our studies that a nonmyeloablative preconditioning regimen can be used to reproduce tolerance to MOG in our EAE model (45). Underpinning this is the observation that only low-level microchimerism is required to promote robust tolerance (45,59). Taken together, the data that are gradually accumulating surrounding this strategy of using a gene therapy approach to tackling autoimmunity will bolster its significance as a feasible and future option for potential clinical translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has successfully induced tolerance to a diverse range of tissues, including kidney [242, 259, 265, 267271], heart [245, 268], skin [245, 255], liver [272275], trachea [251], and vascularized composite tissue allografts (CTA) [255, 257]. It has also successfully reversed autoimmune disorders including SLE [227, 231, 236, 237, 252, 260, 261, 276], Type I diabetes [239, 241, 244, 249, 250, 262], pemphigus vulgaris [276, 277], and experimental allergic encephalomyelitis (a preclinical model for multiple sclerosis) [235, 238, 247, 248, 260, 278]. However, results of clinical trials using HSC transplantation to treat “true” multiple sclerosis have been more mixed; some trials have reported very positive impact on clinical scores and disease progression [278281], while others have found either no improvement at all, or perhaps even a worsening of neuroinflammation and demyelination following HSC transplant [282, 283].…”
Section: Hsc Transplantation To Induce Immunological Tolerance Andmentioning
confidence: 99%